Kharaj dan Agraria: Studi Komparasi Sistem Kharaj Masa Awal lslam dan Agraria di Indonesia - Aji Damanuri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
This study aims to compare the kharaj system in early Islamic times with the agrarian system in Indonesia to understand the similarities and differences in land management and agricultural taxes. The method used is juridical-historical research with a comparative approach through a literature study of classical Islamic sources and agrarian regulations in Indonesia. The results of the study show that kharaj is a land tax system applied in early Islamic rule to regulate land ownership and utilization, while the Indonesian agrarian system is based on the concept of customary rights and modern regulations such as the Basic Agrarian Law (UUPA). Although it has the principle of fairness in land distribution, the kharaj system is more oriented towards state revenue, while Indonesian agrarian law emphasizes the welfare of the people. This study recommends integrating the principle of kharaj justice into modern agrarian policy.